Executive Committee Minutes 2021-06-03 - Academic Senate:::::::::
Agenda Approved. Minutes of 12/5/19 approved. Chair Report. President Report. From SDS: Resolution on Affordable Instruction Materials – referred back to SDS. Provost Report. Vice Chair Report. Vice President for Student Affairs Report. Associated Student Report. Faculty Eligible for Emeritus Status – approved for Senate consent item. From EPC: Pre-Business BS Revision – approved for Senate consent calendar. APARC Report. EPC Report. FSAC Report SAC Report. Senate Agenda approved.